Gender-transformative HIV and SRHR programme approaches for adolescents and young people: a realist review to inform policy and programmes - Isolde Birdthistle; Annabelle Gourlay; Sagri Singh; Damilola Walker; Migena Mata (BMJ Global Health)
Introduction Gender inequalities continue to drive new HIV and sexually transmitted infections (STIs) at rates too high to achieve global goals. In high HIV-burden jurisdictions, this is particularly true for adolescent girls and young women at disproportionate risk, while social and systemic barriers also impede the engagement of young men and gender minorities with health services. We sought evidence of approaches to promote sexual and reproductive health (SRH) outcomes by addressing gender transformation and removing structural barriers that broadly limit prospects for adolescents and young people.Methods We conducted a realist review to identify HIV and SRH-focused interventions with gender transformative mechanisms. Eligible interventions sought to achieve HIV/STI prevention, sexual behaviour or pregnancy outcomes among young people by enhancing agency, resources and social norms supportive of gender transformation. We developed a programme theory to guide the data extraction and synthesis and categorised interventions by strategy, recording impacts on health and/or gender-related outcomes.Results We identified 33 eligible interventions, representing diverse programme strategies and outcomes. Most interventions used a combination approach, with economic strengthening as the most common central strategy (n=13), followed by community-based mobilisation for norms change (n=7), then school-based educational curricula (n=6). The majority (n=24) achieved ‘dual effects’, that is, positive effects on both health and gender-related outcomes; 15 with dual effects specific to HIV prevention. Few evaluations measured or found impacts on HIV/STI incidence. 12 reported positive impacts on condom use alongside improved agency or gender norms.Conclusions Youth-focused interventions that address context-specific economic and social determinants of HIV and SRH risk have proliferated recently, with encouraging impacts on both HIV/SRH and gender-related outcomes. This bodes well for empowering strategies to achieve HIV and STI reduction targets among adolescents and young people, and broader SRH goals. However, most interventions prioritise individual rather than structural change; impeding their ‘gender transformative’ potential.